2013
DOI: 10.2323/jgam.59.011
|View full text |Cite
|
Sign up to set email alerts
|

Application of multiplex PCR assay based on uidR and fliCH7 genes for detection of Escherichia coli O157:H7 in milk

Abstract: A highly sensitive and specific multiplex PCR assay has been developed to detect the presence of Escherichia coli O157:H7 from naturally contaminated raw milk samples within 10 h. The primers explored in the assay were targeted against the uidR gene specific for all types of E. coli and the fliCH7 gene specific for the h7 flagellar antigen of E. coli O157:H7. The multiplex PCR assay developed was found to be highly specific as it produced PCR products of 152 bp (E. coli specific) and 625 bp (E. coli O157:H7 sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Similarly, the detection limits achieved in this study were superior to those of Martinez et al (2001) who achieved a sensibility limit of 100 CFU/mL for the same pathogen. Moreover, a detection limit of 2 CFU/mL was verified, being similar to the one of Kumar et al (2013) that detected E. coli producers of the Shiga toxin (STEC) in samples of milk without pre-enriching. Meiri-Bendek et al (2002) conducted a contamination of milk with different concentrations of S. agalactiae for later detection by PCR.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, the detection limits achieved in this study were superior to those of Martinez et al (2001) who achieved a sensibility limit of 100 CFU/mL for the same pathogen. Moreover, a detection limit of 2 CFU/mL was verified, being similar to the one of Kumar et al (2013) that detected E. coli producers of the Shiga toxin (STEC) in samples of milk without pre-enriching. Meiri-Bendek et al (2002) conducted a contamination of milk with different concentrations of S. agalactiae for later detection by PCR.…”
Section: Discussionsupporting
confidence: 67%
“…Recent advances in diagnostic techniques have made several protocols available for isolation and characterization of E. coli O157:H7 from food, fecal, and environmental samples (Deisingh & Thompson, 2004;Tamerat, Muktar, & Shiferaw, 2016). Further, to classify and elaborate the function of the main virulence genes, such as stx 1 and stx 2 , and genes encoding accessory STEC virulence factors, such as eaeA, hlyA, and flic H7 , different PCR assays have been described (Al-Ajmi et al, 2006;Gannon, King, Kim, & Thomas, 1992;Holland, Louie, Simor, & Louie, 2000;Kumar, Grover, & Kumar Batish, 2013;Pan, Chen, & Su, 2002;Sharma, 2006;Sharma & Dean-Nystrom, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy to mention the findings of Kumar et al (2013), who showed the presence of pathogenic E. coli O157:H7 in pasteurized milk samples. These authors described a higher detection signal after enrichment, suggesting the presence of viable cells after pasteurization or postpasteurization contamination.…”
Section: Preparation Of Template Dnamentioning
confidence: 93%